If it's not what You are looking for type in the equation solver your own equation and let us solve it.
8=8v-49(v+8)
We move all terms to the left:
8-(8v-49(v+8))=0
We calculate terms in parentheses: -(8v-49(v+8)), so:We get rid of parentheses
8v-49(v+8)
We multiply parentheses
8v-49v-392
We add all the numbers together, and all the variables
-41v-392
Back to the equation:
-(-41v-392)
41v+392+8=0
We add all the numbers together, and all the variables
41v+400=0
We move all terms containing v to the left, all other terms to the right
41v=-400
v=-400/41
v=-9+31/41
| 7k+5=5(k-7) | | -36=5w-6 | | 24(x-25)=24 | | g−7/3=7/2 | | 2t-7=17 | | p=2(48+37) | | .25(3p+6)=6p+6 | | f^2+6f+6=0 | | 1/4(8x+16)=2(x=4) | | 5/8h=-10 | | (-24)(2)+(-18)=x | | 52=2y+12 | | -6(4+3)=x | | -2x+4-4=-2 | | -24+(-18)=x | | 49=2y+9 | | 1/2y+1=1/6 | | 1/y+1=1/6y | | 1+9t=82 | | 10x^2-1=269 | | 39=3y-12 | | 4x+5-x=4+6x-11 | | 3/4+1/3x=5+5/6x | | 30=4v-10 | | 98p^2-18=0 | | 9n+4=3n2-0.75 | | 2r^2=114 | | 5w+11=101 | | 3(6x−6)=9(2x−1)-9 | | r+22-10= 1 | | 6+p+3=34-3 | | 4(3x^2-4)=0 |